RAINWATER TRAP TRAPPING THE WATER FROM A GUTTER SYSTEM - Skalska-Kubiak, Jadwiga; Kubiak, Tomasz; Kubiak, Julita; Kubiak, Józef (2024)
The subject of the invention is a rainwater trap trapping water from gutter system that enables collection of rainwater flowing from roofs of buildings, characterized in that it consists of an overflow stub pipe (1) inside which a water pipe (2) is placed, and to the outer (side) wall of the overflow stud pipe (1) there is attached a partition (3) and a pipe (4) for supplying sealing and fixing agent to the partition.